2013
DOI: 10.3390/jfb4040358
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial, Mechanical and Thermal Studies of Silver Particle-Loaded Polyurethane

Abstract: Silver-particle-incorporated polyurethane films were evaluated for antimicrobial activity towards two different bacteria: Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus). Distributed silver particles sourced from silver nitrate, silver lactate and preformed silver nanoparticles were mixed with polyurethane (PU) and variously characterized by field emission scanning electron microscopy (FESEM), fourier transform infra-red (FTIR) spectroscopy, X-ray diffraction (XRD) and contact angle measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 51 publications
3
40
0
Order By: Relevance
“…Of the three membranes tested, the silver-modified nanofibre membrane displayed lowest hydrophilicity due to the hydrophobic nature of the polyurethane nanofibres used during modification. While Paul et al [32] have shown that silver nanoparticles can increase the hydrophilicity of polyurethane nanofibre layers; the silver nanoparticles used in this study had no discernible effect and hydrophilicity was always higher than that of the reference ( Table 3). …”
Section: Wetting Propertiesmentioning
confidence: 85%
“…Of the three membranes tested, the silver-modified nanofibre membrane displayed lowest hydrophilicity due to the hydrophobic nature of the polyurethane nanofibres used during modification. While Paul et al [32] have shown that silver nanoparticles can increase the hydrophilicity of polyurethane nanofibre layers; the silver nanoparticles used in this study had no discernible effect and hydrophilicity was always higher than that of the reference ( Table 3). …”
Section: Wetting Propertiesmentioning
confidence: 85%
“…An adequate amount of free silver ions is required, and while water soluble silver salts can give the necessary high concentrations, this is countered by sequestration by protein and other macromolecules. Loss through insoluble AgCl and chelating to microbial products is an important problem as well 5 . The antimicrobial properties of Ag hold significant promise; the development of bacterial resistance 1,3 , the mechanism of action 6,7 , toxicology 8,9 and clinical utility has been studied greatly for medical applications 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Wet chemistry reduction method of Ag + ion is rapidly and effectively using reducing agent such as Sodium borohydride, Citrate, cellulose, D-glucose etc 3,5,21 . However, one of the disadvantages of these methods is that they are not reduced silver from ions to metallic form at all pH level.…”
Section: Introductionmentioning
confidence: 99%
“…In past decades, the approach most commonly used to address this problem involved modification of citrate on the surface of the nanosilver to obtain acceptable stability. 8,9 Recently, van der Zande reported that the stability of nanosilver appeared to be greatly improved after modification with polyvinylpyrrolidone in comparison with citrate coating, remaining stable for up to 5 months. 10 Further, Paredes et al found that certain amino acids could be used as reducing agents in the preparation of nanosilver.…”
Section: Introductionmentioning
confidence: 99%